TPACK Implementation on Energy Topic: Reading Comprehension and Feasibility of Teaching Material - Zulkarnaen Zulkarnaen; Shelly Efwinda; Nurul Fitriyah Sulaeman (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2023)
This research is the "Development" stage of the type of R&D research with the ADDIE Model (Analyze, Design, Development, Implementation, and Evaluate). The teaching material developed in this study is a Handout entitled "TPACK Implementation on Energy Topic" to improve the teaching skills of pre-service teachers. This study describes the reading comprehension and feasibility of teaching material. The research instrument was a reading comprehension test sheet and a feasibility assessment sheet. The comprehension test was filled in by 184 students at one of the universities in Indonesia from the Department of Physics, Chemistry, and Biology Education. A feasibility Assessment reviewed by experts was conducted. The results showed that 1) The overall reading comprehension of teaching material was in the high level of an understanding category (independent category), 2) The Feasibility Assessment on the graphic and the language feasibility aspect were both in the very feasible category, 3) The Feasibility Assessment on the content feasibility aspect, presentation feasibility aspect, and contextual assessment aspect were all in the very feasible category. Based on these results, it can be concluded that teaching materials can be used in further research to be implemented